BOOTSTRAPPING ANALYSIS OF NORTH SUMATRA PROVINCE INSPECTORATE PERFORMANCE - Silaban, Daniel Ebenezer; Lubis, Irsad (Jurnal Riset Bisnis dan Manajemen, 2023)
The goal of this study is to analyze the factors that influence how well the inspectorate in the province of North Sumatra performs. This research is important because it aims to evaluate the performance of the inspectorate's officials and staff in North Sumatra Province so that measures may be taken to raise employee professionalism and quality. The Smart PLS program was employed as the basis for the quantitative research approach. The research subjects were 48 officials and workers in the functional position of auditors who were taken using the Slovin technique. The results indicate that the inspectorate of the North Sumatra Province performs poorly, particularly when it comes to the implementation of good governance and leadership commitment, where indirect good governance has not been able to mediate leadership commitment.